Những câu hỏi liên quan
NT
Xem chi tiết
AH
25 tháng 10 2024 lúc 23:54

Lời giải:

Đặt $\frac{a}{b}=\frac{c}{d}=k\Rightarrow a=bk; c=dk$. Khi đó:

$\frac{ab}{cd}=\frac{bk.b}{dk.d}=\frac{b^2}{d^2}(1)$

$\frac{a^2-b^2}{c^2-d^2}=\frac{(bk)^2-b^2}{(dk)^2-d^2}=\frac{b^2(k^2-1)}{d^2(k^2-1)}=\frac{b^2}{d^2}(2)$

Từ $(1); (2)$ ta có đpcm

------------------------

Lại có:

$(\frac{a+b}{c+d})^2=(\frac{bk+b}{dk+d})^2=(\frac{b(k+1)}{d(k+1)})^2=(\frac{b}{d})^2(3)$

$\frac{a^2+b^2}{c^2+d^2}=\frac{(bk)^2+b^2}{(dk)^2+d^2}=\frac{b^2(k^2+1)}{d^2(k^2+1)}=\frac{b^2}{d^2}=(\frac{b}{d})^2(4)$

Từ $(3); (4)$ ta có đpcm.

Bình luận (0)
DX
Xem chi tiết
TC
9 tháng 8 2021 lúc 16:50

undefined

Bình luận (0)
BM
Xem chi tiết
L7
Xem chi tiết
L7
1 tháng 3 2022 lúc 22:20

giúp mình với

Bình luận (0)
GL
1 tháng 3 2022 lúc 22:23

Đặt ab=cd=k

 

Khi đó ta có :

a=bk và c=dk

Suy ra :

a2-b2c2-d2=(bk)2-b2(dk)2-d2

=b2k2-b2d2k2-d2

=b2.(k2-1)d2.(k2-1)

=b2d2(1)

Ta lại có :

Bình luận (0)
GL
1 tháng 3 2022 lúc 22:23

 

Đặt ab=cd=k

Khi đó ta có :

a=bk và c=dk

Suy ra :

a2-b2c2-d2=(bk)2-b2(dk)2-d2

=b2k2-b2d2k2-d2

=b2.(k2-1)d2.(k2-1)

=b2d2(1)

Ta lại có :

Bình luận (0)
TN
Xem chi tiết
AH
22 tháng 9 2021 lúc 18:56

Lời giải:

Đặt $\frac{a}{b}=\frac{c}{d}=t\Rightarrow a=bt; c=dt$. Ta có:

$\frac{ab}{cd}=\frac{b^2t}{d^2t}=\frac{b^2}{d^2}(1)$

Mặt khác:

$\frac{(a-b)^2}{(c-d)^2}=\frac{(bt-b)^2}{(dt-d)^2}=\frac{b^2(t-1)^2}{d^2(t-1)^2}=\frac{b^2}{d^2}(2)$

Từ $(1); (2)\Rightarrow \frac{ab}{cd}=\frac{(a-b)^2}{(c-d)^2}$

Bình luận (0)
TT
Xem chi tiết
NA
Xem chi tiết
NL
Xem chi tiết
TH
Xem chi tiết
DT
11 tháng 12 2017 lúc 20:30

ta có :

\(\dfrac{a}{b}\)=\(\dfrac{c}{d}\) \(\Rightarrow\) \(\dfrac{a}{c}\) = \(\dfrac{b}{d}\)

đặt \(\dfrac{a}{c}\) = \(\dfrac{b}{d}\) = k \(\Rightarrow\) a = ck ; b = dk

\(\dfrac{ac}{bd}\) = \(\dfrac{ck.c}{dk.d}\) = \(\dfrac{c^2.k}{d^2.k}\) = \(\dfrac{c^2}{d^2}\) (1)

\(\dfrac{a^2+c^2}{b^2+d^2}\) = \(\dfrac{\left(ck\right)^2+c^2}{\left(dk\right)^2+d^2}\) = \(\dfrac{c^2.k^2+c^2}{d^2.k^2+d^2}\) = \(\dfrac{c^2\left(k^2+1\right)}{d^2\left(k^2+1\right)}\) = \(\dfrac{c^2}{d^2}\)(2)

từ (1) , (2) \(\Rightarrow\) \(\dfrac{ac}{bd}\) = \(\dfrac{a^2+c^2}{b^2+d^2}\)

Bình luận (0)